ANALYSIS OF STUDENTS’ MISCONCEPTION ON DINAMIC MOTION USING THREE-TIER MULTIPLE CHOICE DIAGNOSTIC TEST - Sitri Wuryanti; Yennita Yennita; Fakhruddin Fakhruddin (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2017)
This study aimed to know students’ misconception level on dynamic motion. The subject of this research was all students of XII grade students at SMA Negeri Plus Provinsi Riau with the number were 85 students. It was a survey research. The research data was obtained from the result of three-tier multiple choice diagnostic test with the number of questions were 30 items. Data was analyzed using descriptive analysis techniques. The research result showed that the average of percentage’s students those had misconception on each submaterial were 57.01% for Force and Newton Law, 69.02% for Newton’s Law on Gravity, 49.18% for Work and Energy, 48.24% for Elasticity and Hook’s Law, 59.77% for Momentum, Impulse, and Collision, and 41.47% for Equilibrium and Rotational Dynamic. Generally, the students’ average of percentage those had misconception on dynamic motion was 54.71%. Therefore, it can be conclude that misconception level of XII grade students at SMA Negeri plus Provinsi Riau on dynamic motion is on the middle level.